An investigation into between-meal food desires among hospitalised haematological cancer patients. Issue 2 (April 2016) - Okkels, S.L.; Bredie, W.L.P.; Klausen, T.W.; Beck, A.M.
Summary: Background & aims: Hospitalised haematological cancer patients often suffer from reduced appetite and food intake, which negatively influences the patients' well-being and nutritional status. The aim of this study was to identify specific between-meal food desires in a patient group, in order to increase food intake. The study was conducted using a picture-aided questionnaire, and relating the preferences to factors that could easily be implemented in the hospital menu, such as time of the day and texture. Moreover, the results of the questionnaire were verified by acceptance tests on six selected food items. Methods: A structured 42 items food questionnaire was developed and used to quantify appetitive food desires in patients during morning (11 am) and afternoon (3 pm) sessions. Food items were scored according to patients' preferences and immediate desire to eat. A total of 112 hospitalised haematological cancer patients, screened for nutrition-related symptoms, participated. Univariate statistical models were used to investigate the influence of time-of-day and food texture on between-meal desires. Results: Fresh fruit, ice cream, cheese and mashed potatoes with bacon were the most desired food items. Patients showed significant higher desire to eat in the morning as opposed to the afternoon. Moreover, texture had an influence on food desire, where liquid food was more desired than food with soft or coarse texture. Conclusion: Ranking of food desires among hospitalised cancer patients showed inclination for fresh fruit, ice cream, mashed potatoes with bacon, and cheese. Time of the day (morning) and texture (liquid) had the greatest and most positive impact on food desires. The findings may be easily implemented in hospital food service routines for cancer patients, and might positively contribute to patients' well-being and nutrition.